2017
DOI: 10.1177/0963721417727860
|View full text |Cite
|
Sign up to set email alerts
|

The Pitfalls and Promise of Increasing Racial Diversity: Threat, Contact, and Race Relations in the 21st Century

Abstract: A decades-long trend toward greater racial and ethnic diversity in the United States is expected to continue, with White Americans projected to constitute less than 50% of the national population by mid century. The present review integrates recent empirical research on the effects of making this population change salient with research on how actual diversity affects Whites Americans’ intergroup attitudes and behavior. Specifically, we offer a framework for understanding and predicting the effects of anticipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 45 publications
7
95
3
Order By: Relevance
“…Given recent calls for research examining how changing racial and ethnic demographics may impact intergroup relations (Craig et al, 2017), these findings illustrate the benefits of increasing racial diversity within our society. We found that monoracial POC and multiracial individuals experienced fewer microaggressions and discrimination when living in a diverse context.…”
Section: Resultsmentioning
confidence: 85%
“…Given recent calls for research examining how changing racial and ethnic demographics may impact intergroup relations (Craig et al, 2017), these findings illustrate the benefits of increasing racial diversity within our society. We found that monoracial POC and multiracial individuals experienced fewer microaggressions and discrimination when living in a diverse context.…”
Section: Resultsmentioning
confidence: 85%
“…Several scholars have noted individual ways in which researchers contribute to the generation of knowledge on issues surrounding race and racism, including the use of racially diverse samples (e.g., Richeson, 2018;Stewart & Sweetman, 2018) and examining the effects of racial diversity on individual and collective outcomes (e.g., Bell, Leopold, Berry, & Hall, 2018;Craig, Rucker, & Richeson, 2018;Plaut, Thomas, Hurd, & Romano, 2018;Richeson & Sommers, 2016). Each of these elements is important.…”
Section: Drawing From a Diversity Science Frameworkmentioning
confidence: 99%
“…First, the political salience of other racial and ethnic minority groups, especially Latinos, has been increasing (Abrajano & Hajnal, ; Collingwood, Barreto, & Garcia‐Rios, ). Indeed, the growth and dispersion of the Latino population have been shown to trigger feelings of racial and cultural threat among whites (Craig, Rucker, & Richeson, ; Enos, ; Hopkins, ; Newman, ; Ostfeld, ), increase conservative sentiment and Republican Party support (Craig & Richeson, 2014; Newman, Shah, & Collingwood, ; Reny, Collingwood, & Valenzuela, ), expand support for punitive anti‐immigrant policy (Abrajano & Hajnal, ), and bolster anti‐immigrant policy entrepreneurs at the state and local levels (Gulasekaram & Ramakrishnan, ). While politicians continue to capitalize on anti‐Latino sentiment for electoral gain, little is known about the persuasive effects of implicit and explicit appeals aimed at denigrating Latinos (although see Hopkins & Ostfeld, ).…”
Section: The Ie Model and Anti‐black Appealsmentioning
confidence: 99%